Kinetics and dosimetry of MAb-170: Evaluation of possibilities for intraperitoneal radioimmunotherapy - Alexander, Ch.; Holländer, M.; Schmidt, W.; Kirsch, C.-M. (Nuklearmedizin - NuclearMedicine, 2001)
The monoclonal antibody MAb-170 is directed against adenocarcinomas of different origin. Recent experience in radioimmunoscintigraphy revealed a positive uptake of this MAb in peritoneal metastases of ovarian carcinoma (FIGO lll/IV). Aim: The present investigation should clarify the question whether this antibody could be of use in an adjuvant intraperitoneal radioimmunotherapy (RIT) in patients with minimal residual disease after first-look surgery. Methods: Four patients underwent intraperitoneal application of Tc-99m MAb-170. Subsequent quantitative whole-body scintigraphy, serum and urine sampling were performed for a 48 h period. In one case tumour tissue specimen were sampled during the first surgical procedure 15 h p.L Results: The quantitative evaluation revealed no relevant accumulation in liver, spleen and bone marrow never exceeding 5 % of the whole-body activity. The critical organs are the kidneys that showed 8 to 11 % uptake at 24 h pi. The effective serum curve had a maximum at 24 h pi, the second phase gave a elimination half-time of 53 h. Assuming the worst case, the mean dose to red bone marrow was 0.3 Gy/370 MBq injected dose (ID). Conclusion: These results confirm that a RIT with Re-186 MAb-170 is feasible with activities of up to 3.7 GBq. A kit for labelling MAb-170 with Perrhenate is under investigation.
Keywords: Radioimmunotherapy; monoclonal antibodies; ovarian cancer; peritoneal carcinosis; dosimetry